WHAT ARE THE OPPORTUNITIES OF PRASUGREL IN THE TREATMENT OF PATIENTS WITH ACUTE CORONARY SYNDROME - M. Yu. Gilyarov; Е. V. Konstantinova (Рациональная фармакотерапия в кардиологии, 2018)
The aim of the review is presenting the possibilities and perspectives of the third generation of thienopyridine P2Y12 receptor inhibitor prasugrel in the treatment of patients with acute coronary syndrome (ACS). The main pathogenetic stage of ACS is intracoronary thrombosis, which develops on the surface of a damaged atherosclerotic plaque. The use of acetylsalicylic acid with addition of the second antiplatelet agent, so-called dual antiplatelet therapy, is a standard component in the treatment of any type of ACS, regardless of reperfusion and the selected treatment strategy. Due to some limitations in the use of clopidogrel as the second component of dual antiplatelet therapy, the possibility of prasugrel or ticagrelor usage should be considered in patients with ACS with percutaneous coronary intervention (PCI). Prasugrel therapy is associated with better clinical outcomes as compared with clopidogrel therapy in moderate or high-risk patients who undergo PCI. Because of higher bleeding risk and the lack of clinical benefits in special subgroups of patients, prasugrel must not be used in patients with a stroke or transient ischemic attack in the past. If, after a thorough individual benefit-risk assessment a decision is in favor of prescribing prasugrel to the patient older than 75 years or with a small body weight the maintenance dose of prasugrel is to be reduced by half. Real clinical practice data has shown that with following these recommendations prasugrel demonstrates optimal efficacy, safety, and even more significant impact on the prognosis than this in clinical trials. Prasugrel is able to reduce significantly the incidence of cardiovascular events such as cardiovascular death, myocardial infarction and stroke in patients with ACS who undergo PCI.